Pd-catalyzed annulation of beta-iodovinyl sulfones with 2-halophenols: a general route for the synthesis of 3-sulfonyl benzofuran derivatives - Reddy, Raju Jannapu; Kumar, Jangam Jagadesh; Kumari, Arram Haritha; Krishna, Gamidi Rama (Advanced Synthesis & Catalysis, 2020)
The palladium-catalyzed annulation between beta-iodovinyl sulfones and 2-halophenols or 1-bromo-2-naphthol or 2-bromo-3-pyridinol is presented. The annulation process involving oxa-Michael addition-elimination and intramolecular Heck reaction leading to form 2,3-disubstituted benzofurans (aryl benzofuryl sulfones) in good to high yields. The regioselective tandem construction of C-O and C-C bonds has been achieved with a variety of substitution patterns. Moreover, the tandem process is reliable at gram-scale reactions and a plausible mechanism is also proposed.
Keywords: Benzofurans; beta-Iodovinyl sulfones; Heck reaction; Naphthofurans; oxa-Michael addition

Nickel-catalyzed difunctionalization of alkynyl bromides with thiosulfonates and N-arylthio succinimides: a convenient synthesis of 1,2-thiosulfonylethenes and 1,1-dithioethenes - Kumari, Arram Haritha; Kumar, Jangam Jagadesh; Krishna, Gamidi Rama; Reddy, Raju Jannapu (Synthesis-Stuttgart, 2021)
An efficient nickel-catalyzed vicinal thiosulfonylation of 1bromoalkynes with thiosulfonates in the presence of cesium carbonate is described. An operationally simple and highly regioselective atom transfer radical addition (ATRA) of alkynyl bromides provides a wide range of (E)-1,2-thiosulfonylethenes (alpha-aryl-beta-thioarylvinyl sulfones) in moderate to high yields. The extensive substrate scope of both alkynyl bromides and thiosulfonates is explored with a broad range of functional groups. Indole-derived 1,1- bromoalkenes were also successfully explored in this 1,2-thiosulfonylation process. Moreover, the nickel-catalyzed geminal- dithiolation of alkynyl bromides with N-arylthio succinimides provides 1,1-dithioalkenes in high yields. The present protocol is reliable on gram scale, and a sequential one-pot bromination and thiosulfonylation of phenylacetylene is achieved in a scale-up synthesis. Following control experiments, a plausible mechanism is proposed to rationalize the experimental outcome and the vicinal thiosulfonylation.
Keywords: alkynyl bromides; atom transfer radical addition (ATRA); thiosulfonates; thiosulfonylation; vinyl thiosulfones

Interrupted CuAAC-thiolation for the construction of 1,2,3-triazole-fused eight-membered heterocycles from O-/N-propargyl derived benzyl thiosulfonates with organic azides - Reddy, Raju Jannapu; Waheed, Md; Kumari, Arram Haritha; Krishna, Gamidi Rama (Advanced Synthesis & Catalysis, 2022)
A copper(I)-catalyzed interrupted click-sulfenylation of O-/N-propargyl benzyl thiosulfonates with organic azides has been disclosed. The unified CuAAC-thiolation provides a wide range of triazole-fused eight-membered heterocycles in good to high (51-94%) yields under mild reaction conditions. Moreover, a three-component reaction is also achieved involving O-/N-propargyl benzyl thiosulfonates, benzyl bromide, and sodium azide to deliver fused-triazoles in 61-74% yields. From a synthetic point of view, the present protocol has been demonstrated at gram-scale reactions. A plausible mechanism is also proposed based on experimental results and control experiments.
Keywords: Eight-Membered Heterocycles; Fused-Triazoles; Interrupted-Click Reaction; Thiolation; thiosulfonates

Solvent-driven mono- and bis-sulfenylation of (E)-beta-iodovinyl sulfones with thiols for flexible synthesis of 1,2-thiosulfonylalkenes and 1,2-dithioalkenes - Reddy, Raju Jannapu; Kumari, Arram Haritha; Sharadha, Nunavath; Krishna, Gamidi Rama (Journal of Organic Chemistry, 2022)
The nature of solvent is a key factor for stereoselective mono-and bis-thiolation of (E)-beta-iodovinyl sulfones with thiols under basic conditions. A novel and unprecedented vicinal bisthiolation of (E)-beta-iodovinyl sulfones with thiols under the influence of K2CO3/DMSO at room temperature for quick assembly of (E)-1,2-dithio-1-alkenes is presented. Solvent-induced stereoselective monosulfenylation of (E)-beta-iodovinyl sulfones with thiols has also been established for the synthesis of both (E)- and (Z)-1,2-thiosulfonylethenes in MeCN and MeOH, respectively. Moreover, K2CO3-mediated desulfonylative-sulfenylation of (Z)-1,2-thiosulfonylethenes with thiols in DMSO furnished unsymmetrical (Z)-1,2-dithio-1-alkenes for the first time. The solvent-dependent versatile reactivity of (E)-beta-iodovinyl sulfones has been successfully explored to provide a set of (E)-/(Z)-1,2-dithio-1-alkenes and (E)-/(Z)-1,2-thiosulfonyl-1-alkenes in good to high yields with excellent stereoselectivities. Notably, this operationally simple process utilizes a broad substrate scope with good functional group tolerance and compatibility. The efficacy of the process has been proven for gram-scale reactions, and plausible mechanistic models are outlined on the basis of experimental results and control experiments.